Analisis Tingkat Risiko Penyebab Rel Patah pada Jalur Kereta Api Wilayah Divre IV Tanjung Karang - Nur Anggita Putri, Viola; Usman, Kristianto; Kustiani, Ika; Siregar, Amril Ma’ruf (Departemen Teknik Sipil dan Lingkungan IPB, 2024)
The increase in the volume of passengers and goods in rail transportation in Indonesia has an impact on the condition of railway infrastructure, especially railway infrastructure. The main focus of this condition is the risk of rail damage, especially broken rails. So a holistic assessment approach is needed to identify the root causes and formulate appropriate treatment and improvement strategies. The aim of the research is to identify the factors causing the rail to break and analyze the causes. This research uses a risk level value analysis method by multiplying the results of probability and impact, thus producing a risk value. Risk variables such as extreme rain events, expansion in the alignment area, and mud pumping are high level risks. This is followed by medium, low and very low risks, according to the classification of each risk variable analyzed. Therefore, the priority scale for handling broken rail repairs is grouped based on the risk level value starting from the highest risk to the lowest risk. The conclusion is that risk variables such as extreme rain produce a risk value of IDR 296,881,200 with a probability value of 0.99% and an impact of IDR 29,988,000,000, expansion in the straight area produces a risk value of IDR 376,992,000 with a probability value of 1.10% and impact IDR 34,272,000,000, and mud pumping produces a risk value of IDR 394,128,000 with a probability value of 1.15% and impact IDR 34,272,000,000, these three risk variables are classified as high risk.